2011
DOI: 10.1002/art.30413
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the anticollagen antibody response in a new model of chronic polyarthritis

Abstract: Objective. Type II collagen (CII)-specific B cell responses have been recognized in human rheumatoid arthritis (RA) and in collagen-induced arthritis (CIA). An important limitation of the CIA model is that the CII response and the disease are stimulated by exogenously injected collagen. A model of experimental ovalbumin (OVA)-mediated acute arthritis has been established in which autoimmunity is spontaneous and elicited by antigen-specific T cells. This study was undertaken to create a new model of chronic aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…All together, these data suggested that the adaptive immune response against autoantigens is initiated years before the clinical signs of the disease. Likewise, in certain murine models of arthritis, it has been observed an increase in antibody levels before the onset of clinical symptoms or before the relapse of arthritis [66,67]. Recently, anti-CarP antibodies were detected in mice with collagen-induced arthritis (CIA) and appeared after immunization, which caused local inflammation, combined with the notion that inflammation can induce carbamylation and lead to a break of B cell tolerance to carbamylated proteins [66].…”
Section: Preclinical Immunological Phase In Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…All together, these data suggested that the adaptive immune response against autoantigens is initiated years before the clinical signs of the disease. Likewise, in certain murine models of arthritis, it has been observed an increase in antibody levels before the onset of clinical symptoms or before the relapse of arthritis [66,67]. Recently, anti-CarP antibodies were detected in mice with collagen-induced arthritis (CIA) and appeared after immunization, which caused local inflammation, combined with the notion that inflammation can induce carbamylation and lead to a break of B cell tolerance to carbamylated proteins [66].…”
Section: Preclinical Immunological Phase In Rheumatoid Arthritismentioning
confidence: 99%
“…Recently, anti-CarP antibodies were detected in mice with collagen-induced arthritis (CIA) and appeared after immunization, which caused local inflammation, combined with the notion that inflammation can induce carbamylation and lead to a break of B cell tolerance to carbamylated proteins [66]. Furthermore, in a model of chronic antigen-mediated polyarthritis the production of ACPA, RF, and anti-type II collagen (CII) antibodies was observed in the absence of clinical signs of arthritis and increased before the relapse of arthritis [67].…”
Section: Preclinical Immunological Phase In Rheumatoid Arthritismentioning
confidence: 99%
“…Actually, murine collagen-induced arthritis (CIA) has been a gold standard model of human rheumatoid arthritis (RA). However, an important limitation of the CIA model is that the collagen response and the disease are stimulated by exogenously injected collagen, whereas human RA is characterized by a spontaneous breach of selftolerance [15]. Thus, to be more applicable to the histologic and humoral features of human disease, we developed a model of ovalbumin- (OVA-) mediated polyarthritis, in which autoimmunity is spontaneous [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…Mice were sacrificed four days later and cells were isolated from joint tissue and draining popliteal lymph nodes (pLN). The “late” model antigen induced inflammatory arthritis was modified from a model of chronic polyarthritis(21). 30 days after HAO administration described above, mice were given a second periarticular injection of 100µg of HAO in incomplete Freund’s adjuvant (IFA) (Sigma-Aldrich) or IFA alone as a control.…”
Section: Methodsmentioning
confidence: 99%
“…This will inform the development of more effective tolerogenic therapies by indicating the range of clones that would need to be targeted and the disease stage at which these therapies are most likely to be effective. In this study, we employed breach of self-tolerance models of antigen induced inflammatory arthritis (19,20) and chronic polyarthritis (21) in which autoreactive responses develop. These models also recapitulate the early and later stages of the disease – hereafter named the early and late phases respectively.…”
Section: Introductionmentioning
confidence: 99%